The Export Decision Process: An Empirical Inquiry - Simpson, Claude L.; Kujawa, Duane (Journal of International Business Studies, 1974)
This study profiles export decision-makers in both exporting and nonexporting firms, in terms of their perceptions of the risks and cost/benefit trade-offs associated with exporting, and their reactions to various types of stimuli to export. It concludes an export stimulus (e.g., an unsolicited order from a foreign customer) is a significant but not sufficient condition for a positive export decision, and that important variations between exporters and nonexporters in cost, profit, and risk perceptions may well account for different responses to similar stimuli by these two groups. Present public policies to promote exports are critiqued in light of the findings.